Heat unit requirement and its utilisation efficiency in wheat under different hydrothermal environments - Singh, Sukhvir; Kingra, P.K.; Singh, Som Pal (Annals of Agricultural Research, 2016)
A field experiment was conducted at the Research Farm, School of Climate Change and Agricultural Meteorology, Punjab Agricultural University, Ludhiana during rabi 2013-14. Wheat variety PBW 621 was sown on three dates viz. D1 (29th October), D2 (12th November) and D3 (28th November) and four irrigation levels namely I1 (Irrigation at CRI stage), I2 (Irrigation at CRI and Flag leaf emergence stage), I3 (Irrigation at CRI, flag leaf emergence and soft dough Stage) and I4 (Recommended 4 post sowing irrigations) in randomized block design. D1 took 157 days to attain maturity followed by 151 days taken by D2 and 142 days taken by D3 sown crop. The AGDD and APTU at physiological maturity were higher under D1 (1759.9°C day and 19403.2°C day hr) followed by D2 (1695.3°C day and 18992.6°C day hr) and D3 (1623.2°C day and 18570.2°C day hr) respectively, where as AHTU were higher under D2 (11897.8°C day hr) followed by D1 (11386.9°C day hr) and D3 (11234.2°C day hr). Heat use efficiency w.r.t. straw and grain yield were higher under D1 followed by D2 and D3. Phenophasic models explained 96 to 99% variation in crop phenology due to heat units under D1, 94 to 98% under D2 89 to 97% variation under D3. Heat use efficiency also exhibited positive linear relationship with dry matter production (R2 = 0.99) and grain yield (R2 = 0.87). The study concluded that timely sowing of wheat improves heat use efficiency, which is essentially required under climate warming scenarios